PERKEMBANGAN DAN PERUBAHAN RITEL PADA KONDISI NEW NORMAL PANDEMI COVID-19 DI BANDUNG - Yudha, Eka Purna; Azura, Chiquitita Qinthar; Ramadhani, Nadhifa Zahra; Hendarliana, Asri Nurrizka (Universitas Galuh, 2023)
The business world, such as the retail business, has an important role in breaking the chain of spread of the COVID-19 virus because of the large population, mobility, and interaction between people, so this must be anticipated so that the spread of the virus does not spread. Therefore, this new normal life is important to live in order to break the chain of spread of the COVID-19 virus and the wheels of the economy can continue to run by taking maximum possible precautions and following health protocols to prevent the spread and transmission of the COVID-19 virus from getting wider. Based on the results of the research above, several things can be interpreted, namely the survey states that respondents still prefer to carry out shopping activities offline to traditional retail and modern retail, while the use of online or e-commerce platforms in fulfilling household basic needs is still considered very little. This is supported by the survey results, namely the proportion of